1995
DOI: 10.3109/02813439508996739
|View full text |Cite
|
Sign up to set email alerts
|

The public view on cardiovascular risk factors and changes in lifestyle

Abstract: Knowledge was good about causative cardiovascular risk factors, but poor about healthy eating. Physicians were expected to have an interest in patients' lifestyle and in prevention. This type of knowledge is important for preventive work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The same authors found a low level of motivation for a healthy diet in the same population: two-thirds doubted that they could change their eating habits. 19 This article presents a subgroup analysis of the RELIF (REgularnoe Lechenie I proFilaktika) multicenter study concerning interest and motivation of patients with arterial hypertension (AH) for lifestyle and risk factor modification, as well as counseling and recommendations given by their GPs.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors found a low level of motivation for a healthy diet in the same population: two-thirds doubted that they could change their eating habits. 19 This article presents a subgroup analysis of the RELIF (REgularnoe Lechenie I proFilaktika) multicenter study concerning interest and motivation of patients with arterial hypertension (AH) for lifestyle and risk factor modification, as well as counseling and recommendations given by their GPs.…”
Section: Introductionmentioning
confidence: 99%
“…There are ethical consequences involved, since treatment may lead to perceptions of illness when the 'healthy' patient becomes medicalized [9,10]. Information on indicators of risk for cardiovascular events, and the risks of lifestyle factors is frequently featured in the mass media, and public awareness has been considered high in Sweden [11]. During recent years, different models have been introduced for calculating and scoring risk as aids to treatment decisions [12].…”
Section: Introductionmentioning
confidence: 99%
“…A postal questionnaire was issued, with reminders when necessary. Forty-four questions were the same as in 1990, and five follow-up questions were added (10). The questions concerned the subjects' knowledge of and attitudes to cardiovascular risk factors, primarily hyperlipidaemia, views concerning treatment and sources of medical information.…”
Section: Methodsmentioning
confidence: 99%